Periodic Solutions of Abstract Neutral Functional Differential Equations - Henriquez-Miranda, H (2012)
We characterize the existence of periodic solutions of some abstract neutral functional differential equations with finite and infinite delay when the underlying space is a UMD space. © 2011 Elsevier Inc.